Kajian Interaksi Nanoemulsi Silymarin-Carbon-Dots secara In Vitro pada Sel 3T3/NIH, MCF-7, dan MDA-MB Menggunakan Mikroskop Konfokal - Heni Rachmawati; Yogie Handoko; Juniar Kalpika Resmi (PT Dexa Medica, 2023)
Silymarin is a natural compound from Silybum marianum which has potential to treat various liver diseases, but it has low bioavailability. This study aimed to develop silymarin-carbon dot nanoemulsion, analyze its parameters, and its interaction with various cell lines. Nanoemulsion oil phase was prepared from castor oil: cremophore RH40 (surfactant): PEG400 (co-surfactant) with a ratio 1:8:1. Mild stirring method was applied for nanoemulsion preparation followed by characterization including, visual appearance, droplet size, polydispersity index, zeta potential, entrapment efficiency, and physicochemical stability under normal storage condition for 2 weeks. Toxicity determined by IC50 using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] method using NIH/3T3, MCF-7, and MDA-MB cells. Nanoemulsion penetration ability was compared to silymarin solution on MCF-7 cell using confocal microscope after 3 and 6-hours incubation. The results of droplet measurement, zeta potential, polydispersity index, and entrapment efficiency was 27,95 ± 4,31 nm, 0,296 ± 0,09, -11,81 mV, and 91,92 ± 0,04%, respectively. According to stability data, the nanoemulsion showed no significant changes in the entrapment efficiency as well as the physical characteristic. The IC50 value of silymarin nanoemulsion and solution was 30,67µg/ml and 45,40µg/ml for MCF-7, and was 37.50 µg/ml and 39.14 µg/ml for MDA-MB. The nanoemulsion containing silymarin is potential to penetrate MCF-7 cell line at concentration of 12.5 µg/ml both after three and six-hours incubation. The developed nanoemulsion is a promising system to improve the therapeutic value of sylimarin.